2011
DOI: 10.1186/1746-4269-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of the Monpa ethnic group at Arunachal Pradesh, India

Abstract: BackgroundThe present paper documents the uses of plants in traditional herbal medicine for human and veterinary ailments, and those used for dietary supplements, religious purpose, local beverage, and plants used to poison fish and wild animals. Traditional botanical medicine is the primary mode of healthcare for most of the rural population in Arunachal Pradesh.Materials and methodsField research was conducted between April 2006 and March 2009 with randomly selected 124 key informants using semi-structured q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 50 publications
6
60
1
Order By: Relevance
“…Regarding the choice of MPs in the indigenous medical systems, factors such as ease of collection, accessibility, and affordability appear to be major determinants (Pannozzo et al, 2012). Results of our ethnobotanical study (e.g., medicinal and other uses of plant resources: Table 3) are comparable to what Namsa et al (2011) documented previously for the Monpa tribe of Kalaktang, Arunachal Pradesh, India, and Prakash (2011) for the tribals of Uttar Pradesh in India, implying strong similarities in the usage of MP resources by the tribal communities of the Eastern Himalayan belt. Apart from this, MPs in Bhutan have been a cardinal source of food and food supplements, socioeconomic and religious uses too (Wangchuk et al, 2008;Wangchuk and Olsen, 2011).…”
Section: Ethnobotanical and Socioeconomic Aspectssupporting
confidence: 73%
See 1 more Smart Citation
“…Regarding the choice of MPs in the indigenous medical systems, factors such as ease of collection, accessibility, and affordability appear to be major determinants (Pannozzo et al, 2012). Results of our ethnobotanical study (e.g., medicinal and other uses of plant resources: Table 3) are comparable to what Namsa et al (2011) documented previously for the Monpa tribe of Kalaktang, Arunachal Pradesh, India, and Prakash (2011) for the tribals of Uttar Pradesh in India, implying strong similarities in the usage of MP resources by the tribal communities of the Eastern Himalayan belt. Apart from this, MPs in Bhutan have been a cardinal source of food and food supplements, socioeconomic and religious uses too (Wangchuk et al, 2008;Wangchuk and Olsen, 2011).…”
Section: Ethnobotanical and Socioeconomic Aspectssupporting
confidence: 73%
“…The top most species in this respect were: S. chirata, P. polyphylla, R. cordifolia, P. confertiflora, and V. nepalense. The total number of MPs in the present study was greater than that of what Namsa et al (2011) reported for Sikkim (50 plants species belonging to 29 families used for treating 22 human and four veterinary ailments) and lower than that of what earlier reported for Bhutan (113 lower elevation medicinal plants). Species composition is often determined and regulated by an array of ecological, environmental, edaphic and anthropogenic factors (Muraleedharan et al, 2005).…”
Section: Discussion Floristic Attributescontrasting
confidence: 55%
“…Iran produced 89960 Tons medicinal plants and exported 2588 tons with exports income of 8052 thousand US $. (Ghahreman, 1974;Namsa et al, 2011;Sabzian, 2008;WHO, 2001). …”
mentioning
confidence: 99%
“…Number of studies such as Enayet Hossain, 2007;Giday et al, 2009;Osawaru and Dania-Ogbe, 2010;Rout et al, 2010;Namsa et al, 2011 have documented valuable information on traditional use of medicinal plants. Also some studies (Moreno-Salazar et al, 2008;Dey and De, Our Nature 2013, 11(2): 177-186 2012; Kadir et al, 2013) have been carried out particularly for gastrointestinal disorders.…”
Section: Introductionmentioning
confidence: 99%